Rekrutmen dan Penilaian Kinerja SDM di Koperasi ISM Karya Sinar Bahari, Desa Tanggul Jaya, Kelurahan Banten, Kecamatan Kasemen, Kota Serang, Provinsi Banten - Mansur, Mansur; Jurnal, Jurnal; Fauzi, Moh.; Dewi, Cynthia; Hefniwati, Ella; Mukrodi, Mukrodi; Sachro, Sachro (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This service is entitled Recruitment and HR performance assessment at the ISM Karya Sinar Bahari Cooperative, Tangul Jaya Village, Banten Subdistrict, Kasemen District, Serang City, Banten Province. This service was carried out on Saturday, August 3 2024, which was attended by 22 students and 1 supervisor at Pamulang University. This Community Service aims to analyze the recruitment process and performance assessment of human resources (HR) at the ISM Karya Sinar Bahari Cooperative, Tanggul Jaya Village, Banten Village, Kasemen District, Serang City, Banten Province. The ISM Karya Sinar Bahari Cooperative is an economic institution that plays an important role in improving the welfare of its members and the surrounding community. However, the main challenge faced is how to recruit quality human resources and carry out performance assessments effectively to ensure the achievement of cooperative goals. This Community Service uses survey methods and direct material delivery as well as simulations and discussions regarding management, financial management and product marketing via WhatsApp Business. This Community Service activity succeeded in providing understanding to ISM Karya Sinar Bahari Cooperative Members regarding Recruitment and performance assessment, Financial Management and Product marketing via business WhatsApp social media. In this way, it is hoped that this cooperative can improve the quality of its human resources and, in turn, strengthen its competitiveness and contribution to the welfare of its members and society.